LEKSEM BERMAKNA ‘MENGELUPAS’ DALAM BAHASA JAWA - Sri Nardiati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
The paper describes a group of Javanese peeled lexemes that show closely related in meaning and subsumed under a general lexeme based on the theory of componential analysis of meaning and the theory of semantic fields. These lexemes can be classified into two semantic fields. The first is included under the r ( zero) superordinate supeordinate lexeme and the second included under nglokop superordinate laxeme.